Auditoria integral y su incidencia en la gestión administrativa de liga deportiva Cantonal Quevedo, período 2021 - Haro Párraga, Magaly Yajahira (2023)
The objective of this work is to evaluate the incidence of the integral audit in the administrative management of “Liga Deportiva Cantonal Quevedo” using the theoretical framework based on the conceptual, theoretical, and legal foundation of the investigation. The inductive, deductive, historical-logical and descriptive methods were applied, using observations and reviews of documents examining compliance with recommendations issued in the report of the State Comptroller's Office of the audit of the period 2011-2016; and later the levels of internal control were measured through the application of the COSO 1 form, in addition the assigned budget related to the Manual Operating Plan was evaluated, as well as determining the appearance of two important findings relevant to transparency and multiple employment. As a result of the investigation, it was possible to determine that the level of internal control of the administrative, financial processes and compliance with the recommendations correspond to a low level of confidence as well as a high level of risk, it was also evidenced that when reviewing the documents and operations carried out did not reach 100% compliance with the budget of the Annual Operating Budget, with a reprogramming that translates into a lack of planning; In conclusion, there is a lot of work to be done to improve administrative management at the entity level, as well as the delivery of recommendations that seek to optimize administrative processes and results that can later be transferred to sports management with high standards.